Upaya Pemerintah Kota Pekanbaru melalui Inovasi SIPINTAR PEDULI dalam Pemenuhan Identitas Kependudukan Orang Terlantar - Weni Puji Hastuti; Tiana Syaputri (Al-Manar Journal of Public Administration and Management, 2026)
This research was conducted at the Population and Civil Registration Office of Pekanbaru City with the aim of finding out how the innovation of the service system to complete the identity of abandoned people (SIPINTAR PEDULI) by the Population and Civil Registration Office of Pekanbaru City and to find out the factors that inhibit the innovation of the service system to complete the identity of abandoned people (SIPINTAR PEDULI) by the Population and Civil Registration Office of Pekanbaru City. This research uses a qualitative approach with a descriptive method. Data collection techniques used include interviews, observation, and documentation. This research is based on five indicators, namely relative advantages, suitability, complexity, possibility to try, and ease of observation. The results of this study indicate that the innovation of the service system to complete the identity of abandoned people (SIPINTAR PEDULI) by the Pekanbaru City Population and Civil Registration Service has not run optimally, this is due to several factors inhibiting the innovation of the service system to complete the identity of abandoned people (SIPINTAR PEDULI) by the Pekanbaru City Population and Civil Registration Service, namely the lack of socialization of website-based services, network limitations in accessing the website, and low public awareness of the importance of identity.